Development of a set of novel binary expression vectors for plant gene function analysis and genetic transformation - Wang, Xiuyuan; Teng, Chong; Wei, Huitian; Liu, Shuang; Xuan, Hongzhuan; Peng, Wentao; Li, Qianqian; Hao, Hongyan; Lyu, Qingya; Lyu, Shanhua; Fan, Yinglun (Frontiers in Plant Science, 2023)
With the advent of multiple omics and Genome-Wide Association Studies (GWAS) technology, genome-scale functional analysis of candidate genes is to be conducted in diverse plant species. Construction of plant binary expression vectors is the prerequisite for gene function analysis. Therefore, it is of significance to develop a set of plant binary expression vectors with highly efficient, inexpensive, and convenient cloning method, and easy-to-use in screening of positive recombinant in Escherichia coli. In this study, we developed a set of plant binary expression vectors, termed pBTR vectors, based on Golden Gate cloning using BsaⅠ restriction site. Foreign DNA fragment of interest (FDI) can be cloned into the destination pBTR by one-step digestion–ligation reaction in a single tube, and even the FDI contains internal BsaⅠ site(s). Markedly, in one digestion–ligation reaction, multiple FDIs (exemplified by cloning four soybean Glyma.02g025400, Glyma.05g201700, Glyma.06g165700, and Glyma.17g095000 genes) can be cloned into the pBTR vector to generate multiple corresponding expression constructs (each expression vector carrying an FDI). In addition, the pBTR vectors carry the visual marker, a brightness monomeric red fluorescent protein mScarlet-I, that can be observed with the unaided eye in screening of positive recombinants without the use of additional reagents/equipment. The reliability of the pBTR vectors was validated in plants by overexpression of AtMyb75/PAP1 in tomato and GUSPlus in soybean roots via Agrobacterium rhizogenes-mediated transformation, promoter activity analysis of AtGCSpro in Arabidopsis via A. tumefaciens-mediated transformation, and protein subcellular localization of the Vitis vinifera VvCEB1opt in tobacco, respectively. These results demonstrated that the pBTR vectors can be used in analysis of gene (over)expression, promoter activity, and protein subcellular localization. These vectors will contribute to speeding up gene function analysis and the process of plant molecular breeding.